Factors influencing technical competencies in digital marketing of MSMEs in wholesale and retail sectors: the mediating role of core competencies - Buaprommee, Nathamon; Cuijten, Nachayapat; Inmor, Sureerut; Suwannahong, Rungsan; Wongpun, Sukontip (Business: Theory and Practice, 2025)
While technology is essential for the survival of micro, small, and medium-sized businesses (MSMEs), their ability to use digital marketing effectively, especially in the wholesale and retail sectors, remains unclear. The study aims to investigate the current state of digital marketing capabilities and the influence of behavioral competencies on technical competencies through the core competencies in digital marketing. The research approach included surveying a sample size of 400 MSMEs in the wholesale and retail sectors. The collected data was analysed using a combination of descriptive statistics and structural equation modelling approaches. This study highlights the crucial role of core competencies in digital marketing. It suggests that strong behavioral skills positively influence technical skills by first impacting core competencies. The findings of this research show that improving behavioral and core competencies has a substantial and positive impact on the technical competencies in digital marketing. Including, the primary goal of developing digital marketing abilities should be to hone behavioral and core competencies since they will contribute to a demonstrable enhancement in the technical competencies of digital marketing.